2011 IEEE Symposium on Computational Intelligence for Security and Defense Applications (CISDA) 2011
DOI: 10.1109/cisda.2011.5945945
|View full text |Cite
|
Sign up to set email alerts
|

Motivating the inclusion of meteorological indicators in the CTBT feature-space

Abstract: Abstract-Verification of the Comprehensive Test-Ban-Treaty (CTBT), as a Pattern Recognition (PR) problem, has been proposed based on four radioxenon features. It has been noted, however, that in many cases this limited feature set is insufficient to distinguish radioxenon levels effected by an explosion from those that are solely products of industrial activities. As a means of improving the detectability of low-yield clandestine nuclear explosions, this paper motivates the inclusion of meteorological indicato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Stocki et al 4 used several binary classifiers to discriminate between the background and synthesized explosion data and demonstrated that these methods outperformed simple linear discriminators. Following this study, Bellinger et al [21][22][23] noted the "unnatural" a priori class probabilities that were inherent in the publicly available Health Canada CTBT data set, highlighting that the domain clearly fits into a 1-class classification problem. This motivated them to develop a stochastically episodic event modeling and simulation framework; the data used for our work were based on this framework.…”
Section: Ctbt Domain 531 Domain Descriptionmentioning
confidence: 82%
“…Stocki et al 4 used several binary classifiers to discriminate between the background and synthesized explosion data and demonstrated that these methods outperformed simple linear discriminators. Following this study, Bellinger et al [21][22][23] noted the "unnatural" a priori class probabilities that were inherent in the publicly available Health Canada CTBT data set, highlighting that the domain clearly fits into a 1-class classification problem. This motivated them to develop a stochastically episodic event modeling and simulation framework; the data used for our work were based on this framework.…”
Section: Ctbt Domain 531 Domain Descriptionmentioning
confidence: 82%